IMPLEMENTASI PENGINDERAAN JAUH DAN SIG UNTUK INVENTARISASI DAERAH RAWAN BENCANA LONGSOR (PROPINSI LAMPUNG) - Samsul Arifin; Ita Carolita; Gothot Winarso (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2006)
Landslide is a phenomena of nature that is very potential to cause damage and the loss human life or material, although the loss is temporarily but the degraded land in the long run affects the lives of the local community. Therefore, to anticipate the occurance with mare casualties, thus a research to inventory potential landslide hazard is necessary to carry out. The implemanted model to detemine region of landslide hazard is Indeks Storie Model approach by implementing remote sensing data and geographic information system (GIS). Based on the analysis result, Lampung Provice have 5 stages of landslide hazard namely : very high, high, medium low and very low, with result of weight values between 0.001-1.68. Generally, Lampung province is quite safe against landslide, while region predicted as landslide hazard are found in 3 district which are West Lampung Regency, Tanggamus and some in North Lampung Regency.